Why do trends in social fluidity at labour market entry and occupational maturity differ? Evidence from Germany and the UK. (February 2023) - Trinh, Nhat An
Abstract: This study examines how intra generational class mobility can lead to differing over-time trends in inter generational class mobility depending on when class destination is measured in individuals' careers. Specifically, it tackles the puzzle why increases in social fluidity are observed when class destination is measured at labour market entry, while only trendless fluctuation is found when class destination is measured 15 years later in Germany and the UK. Using data from the German Socio-Economic Panel (1984–2019) and the UK Household Longitudinal Survey (2009–2020) on respondents entering the labour market during the second half of the twentieth century, the analyses show that this divergence is driven by increases in 'counter mobility' that are subject to country-specific patterns. In the UK, rising counter mobility results from a growing proportion of individuals from salariat origins who enter the labour market in a lower class position but experience upward career mobility. In Germany, it is driven by a rising proportion of individuals from working class backgrounds who start their careers in a higher class but experience downward career mobility. No evidence for origin-specific changes in the relative importance of upward and downward career mobility is found. The results provide a strikingly similar picture for women and men in either country.